Advances of the functionalized carbon nitrides for electrocatalysis. Issue 2 (12th January 2022) - Fan, Qianqian; Su, Jianan; Sun, Tao; Bi, Zenghui; Wang, Huaisheng; Zhang, Shusheng; Liu, Qingju; Zhang, Longzhou; Hu, Guangzhi
Abstract: Over the past few decades, the design and development of carbon materials have occurred at a rapid pace. In particular, these porous graphene‐like carbon nitride materials have received considerable attention due to their superior structures and performances in the energy transformation field. In this review, nitrogenated holey two‐dimensional graphene and polymeric carbon nitride will be discussed in depth. The structural properties, synthetic methods, and applications including electrocatalytic reactions, such as hydrogen evolution reaction, oxygen reduction reaction, oxygen evolution reaction, and nitrogen reduction reaction, will be presented in detail. Finally, we will present the outlooks on the current obstacles to the development of carbon nitride materials. This comprehensive understanding will help guide and motivate researchers to develop and modify carbon nitride materials with better properties in the future. Abstract : In this review, the detailed fabrication strategies and wide applications in the electrocatalysis of carbon nitrides, namely, C2 N and polymeric carbon nitride (PCN), are presented. In‐depth structure–property relations are discussed to provide the fundamental understanding of the reaction mechanism of carbon nitrides toward electrocatalysis.